Efektivitas Gamifikasi Wordwall dalam Meningkatkan Keterampilan Communication Siswa Abad 21 - Azijatul Fitria; Muhammad Hasan Asnawi (IEC: Journal of Educational Innovation, 2026)
This study aims to measure the effectiveness of Wordwall gamification in improving students’ 21st-century communication skills in the Clinometer Tower project. The study employed a quantitative approach using a pre-experimental One-Group Pretest-Posttest Design. The sample consisted of 35 students from class X6 at Gambiran State High School 1, selected through purposive sampling. The instrument, a communication skills questionnaire (indicators: expressing opinions, asking questions, discussing, presenting work results), has been proven to be valid (calculated r for pre-test: 0.823–0.935; post-test: 0.797–0.918) and reliable (Cronbach’s Alpha pre-test: 0.968; post-test: 0.937; very high category). Data analysis included the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank Test, the N-Gain test, and Rosenthal’s effect size. The research results showed a significant difference in communication skills before and after the intervention (Asymp. Sig. (2-tailed) < 0.001; Z = -4.870). Learning observations showed an average communication skills percentage of 72.9% (in the communicative category). However, the N-Gain test yielded an average value of 0.0704 (7.04%; low category), and Rosenthal’s effect size was 0.0651 (very small effect category). It was concluded that the use of Wordwall gamification in the Menara Klinometer project had a statistically significant effect on improving students’ 21st-century communication skills. Still, the results were not yet optimal in practice. Continued learning and intensive practice are needed to achieve maximum improvement.